Formulasi Nutrasetikal Permen Jeli dari Lempuyang Gajah (Zingiber Zerumbet L.) untuk Menambah Nafsu Makan Anak - priskila, onny; Ang, Suryawan; ., Mellisa; Mufida Sari, Laili (Jurnal Kesehatan, 2023)
The problem of eating disorders in children can cause health problems, so a strategy is needed for feeding children, one of which is herbal lempuyang. Gummy candy is a soft, jeli-like confectionery product that has an attractive color, smell, taste, and shape and is easy to chew. The purpose of this study was to make a nutraceutical formulation of gummy candy from lempuyang gajah and find out its benefits in increasing children's appetite. This research is experimental, with pre- and post-test designs. Lempuyang Gajah gummy candy is made with three formulations: 25 gram, 20 gram, and 15 gram. The three formulations were tested on respondents aged 6–10 years in each gramoup of 10 children for 1 week. The selection of respondents was based on the inclusion and exclusion criteria. Measuring the increase in appetite is proven by measuring the increase in weight of the child after treatment. According to the results of this study, the three formulations have a yellowish color, smell like candy, a sweet taste, and are solid and chewy. Giving lempuyang gajah gummy candy at levels of 25, 20, and 15 gramams is proven to increase body weight, but only at levels of 25 gramams does it give statistically significant results with a p-value of 0,000. Improvements in children's appetite were measured by interviews with the parents of respondents about their children's eating habits. The result was an increase in children's appetite in the gramoup with 25 gramams of lempuyang, with a significant value of 0,016.